(untitled) (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
This article examines the different types of feedback, its effects on student engagement and performance, and best practices for incorporating feedback into teaching methods. By understanding and applying effective feedback strategies, educators can create a more dynamic and supportive learning environment.